Study on the tendency of technical-economic evolution of vegetal agricultural products - Ana Ursu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The aim of the paper is to investigate the evolution of agricultural production in rice, soybean and sugar beet crops, revealing their tendencies, as well as the main favorable or restrictive factors, the economic-social effects they generate and the formulation of possible solutions for production development. The study is based on the quantitative and qualitative analysis of the available statistical data series. The calculated indicators highlight the variability of the cultivated area, the yield per hectare, the prices, but also the trade balance. The place of each crop is examined from the point of view of the indicators studied and some conclusive remarks are made regarding the current state of economic development of the plant sector and of the studied plants.
Keywords: Q01; Q15; Q16; 330; agricultural products; technical-economic indicators; economic-social effects